Firm non-market capabilities and the effect of supranational institutional safeguards on the location choice of international investments - Albino-Pimentel, Joao; Dussauge, Pierre; Shaver, J. Myles (Strategic Management Journal, 2018)
[Research summary: We investigate the extent to which firms rely on supranational institutional safeguards versus their non-market capabilities to offset the risks of investing abroad. We argue that firms with non-market capabilities are insensitive to supranational institutional safeguards when choosing the location of their international investments. We show that supranational agreements between an investor's home and host nation, operationalized as bilateral investment treaties (BITs), increase the likelihood of investment, but there is substantial firm heterogeneity with respect to this relationship. Firms with various forms of non-market capabilities are not sensitive to BITs, whereas other firms are more likely to invest under BITs. We advance the understanding of how firm non-market capabilities can substitute for supranational institutional arrangements in addressing risks associated with host country institutional weaknesses. Managerial summary: The risk of expropriation is one of the main concerns companies have when investing abroad. Because of this, many countries implement bilateral investment treaties (BITs) to safeguard foreign investments, alleviate foreign investor concerns, and promote investments. We show that only those companies without political competence or political connections favor countries with BITs when choosing where to invest. Companies with political competence or political connections, on the other hand, ignore BITs and apparently rely on their ability to influence governments whenever their foreign investments face expropriation threats. As a result, politically connected or competent companies can enter markets most of their competitors lacking these capabilities shy away from. They can, therefore, do business in environments in which they face less competition.]